Location via proxy:   [ UP ]  
[Report a bug]   [Manage cookies]                

waganesh (2)

Download as docx, pdf, or txt
Download as docx, pdf, or txt
You are on page 1of 13

To find the area of the triangle with vertices A(1,2,1)A(1, 2, 1)A(1,2,1), B(−3,4,6)B(-3, 4,

6)B(−3,4,6), and C(1,8,3)C(1, 8, 3)C(1,8,3), we can use the formula for the area of a triangle in
three-dimensional space given by the vertices A⃗\vec{A}A, B⃗\vec{B}B, and C⃗\vec{C}C:

Area=12∥AB⃗×AC⃗∥\text{Area} = \frac{1}{2} \|\vec{AB} \times \vec{AC}\|Area=21∥AB×AC∥

First, we calculate the vectors AB⃗\vec{AB}AB and AC⃗\vec{AC}AC:

AB⃗=B⃗−A⃗=(−3−1,4−2,6−1)=(−4,2,5)\vec{AB} = \vec{B} - \vec{A} = (-3 - 1, 4 - 2, 6 - 1) = (-4,


2, 5)AB=B−A=(−3−1,4−2,6−1)=(−4,2,5) AC⃗=C⃗−A⃗=(1−1,8−2,3−1)=(0,6,2)\vec{AC} = \vec{C}
- \vec{A} = (1 - 1, 8 - 2, 3 - 1) = (0, 6, 2)AC=C−A=(1−1,8−2,3−1)=(0,6,2)

Next, we compute the cross product AB⃗×AC⃗\vec{AB} \times \vec{AC}AB×AC:

AB⃗×AC⃗=∣i^j^k^−425062∣\vec{AB} \times \vec{AC} = \begin{vmatrix} \hat{i} & \hat{j} & \


hat{k} \\ -4 & 2 & 5 \\ 0 & 6 & 2 \end{vmatrix}AB×AC=i^−40j^26k^52

Calculating the determinant:

AB⃗×AC⃗=i^∣2562∣−j^∣−4502∣+k^∣−4206∣\vec{AB} \times \vec{AC} = \hat{i} \begin{vmatrix} 2


& 5 \\ 6 & 2 \end{vmatrix} - \hat{j} \begin{vmatrix} -4 & 5 \\ 0 & 2 \end{vmatrix} + \hat{k} \
begin{vmatrix} -4 & 2 \\ 0 & 6 \end{vmatrix}AB×AC=i^2652−j^−4052+k^−4026

Calculating each of the 2x2 determinants:

1. For i^\hat{i}i^:

∣2562∣=(2)(2)−(5)(6)=4−30=−26\begin{vmatrix} 2 & 5 \\ 6 & 2 \end{vmatrix} = (2)(2) -


(5)(6) = 4 - 30 = -262652=(2)(2)−(5)(6)=4−30=−26

2. For −j^-\hat{j}−j^:

∣−4502∣=(−4)(2)−(5)(0)=−8\begin{vmatrix} -4 & 5 \\ 0 & 2 \end{vmatrix} = (-4)(2) - (5)


(0) = -8−4052=(−4)(2)−(5)(0)=−8

Thus, −j^-\hat{j}−j^ gives +8j^+8\hat{j}+8j^.

3. For k^\hat{k}k^:

∣−4206∣=(−4)(6)−(2)(0)=−24\begin{vmatrix} -4 & 2 \\ 0 & 6 \end{vmatrix} = (-4)(6) -


(2)(0) = -24−4026=(−4)(6)−(2)(0)=−24

Putting it all together:

AB⃗×AC⃗=−26i^+8j^−24k^\vec{AB} \times \vec{AC} = -26\hat{i} + 8\hat{j} - 24\


hat{k}AB×AC=−26i^+8j^−24k^
Now, we find the magnitude of this vector:

∥AB⃗×AC⃗∥=(−26)2+82+(−24)2\|\vec{AB} \times \vec{AC}\| = \sqrt{(-26)^2 + 8^2 + (-


24)^2}∥AB×AC∥=(−26)2+82+(−24)2

Calculating:

=676+64+576=1316= \sqrt{676 + 64 + 576} = \sqrt{1316}=676+64+576=1316

Now, calculating the area of the triangle:

Area=121316=12⋅2329=329\text{Area} = \frac{1}{2} \sqrt{1316} = \frac{1}{2} \cdot 2\


sqrt{329} = \sqrt{329}Area=211316=21⋅2329=329

Thus, the area of the triangle is

329.\boxed{\sqrt{329}}.329.

𝐴(1,2,5), 𝐵(4,8,1), 𝐶(−3,2,3),𝐷(0,3,9).


2.Find the volume and surface area of the parallelepiped having adjacent edges defined by

ChatGPT said:

ChatGPT

To find the volume and surface area of the parallelepiped defined by the vertices A(1,2,5)A(1, 2,
5)A(1,2,5), B(4,8,1)B(4, 8, 1)B(4,8,1), C(−3,2,3)C(-3, 2, 3)C(−3,2,3), and D(0,3,9)D(0, 3,
9)D(0,3,9), we need to first define the vectors corresponding to the adjacent edges emanating
from point AAA.

Step 1: Define the vectors

1. Vector AB⃗\vec{AB}AB from AAA to BBB:

AB⃗=B⃗−A⃗=(4−1,8−2,1−5)=(3,6,−4)\vec{AB} = \vec{B} - \vec{A} = (4 - 1, 8 - 2, 1 - 5) =


(3, 6, -4)AB=B−A=(4−1,8−2,1−5)=(3,6,−4)

2. Vector AC⃗\vec{AC}AC from AAA to CCC:

AC⃗=C⃗−A⃗=(−3−1,2−2,3−5)=(−4,0,−2)\vec{AC} = \vec{C} - \vec{A} = (-3 - 1, 2 - 2, 3 -


5) = (-4, 0, -2)AC=C−A=(−3−1,2−2,3−5)=(−4,0,−2)

3. Vector AD⃗\vec{AD}AD from AAA to DDD:

AD⃗=D⃗−A⃗=(0−1,3−2,9−5)=(−1,1,4)\vec{AD} = \vec{D} - \vec{A} = (0 - 1, 3 - 2, 9 - 5) =


(-1, 1, 4)AD=D−A=(0−1,3−2,9−5)=(−1,1,4)
Step 2: Volume of the parallelepiped

The volume VVV of the parallelepiped defined by vectors AB⃗\vec{AB}AB, AC⃗\vec{AC}AC,


and AD⃗\vec{AD}AD is given by the absolute value of the scalar triple product:

V=∣AB⃗⋅(AC⃗×AD⃗)∣V = |\vec{AB} \cdot (\vec{AC} \times \vec{AD})|V=∣AB⋅(AC×AD)∣

Calculate the cross product AC⃗×AD⃗\vec{AC} \times \vec{AD}AC×AD:

AC⃗×AD⃗=∣i^j^k^−40−2−114∣\vec{AC} \times \vec{AD} = \begin{vmatrix} \hat{i} & \hat{j} & \


hat{k} \\ -4 & 0 & -2 \\ -1 & 1 & 4 \end{vmatrix}AC×AD=i^−4−1j^01k^−24

Calculating the determinant:

AC⃗×AD⃗=i^∣0−214∣−j^∣−4−2−14∣+k^∣−40−11∣\vec{AC} \times \vec{AD} = \hat{i} \


begin{vmatrix} 0 & -2 \\ 1 & 4 \end{vmatrix} - \hat{j} \begin{vmatrix} -4 & -2 \\ -1 & 4 \
end{vmatrix} + \hat{k} \begin{vmatrix} -4 & 0 \\ -1 & 1 \end{vmatrix}AC×AD=i^01−24−j^
−4−1−24+k^−4−101

Calculating the 2x2 determinants:

1. For i^\hat{i}i^:

∣0−214∣=(0)(4)−(−2)(1)=0+2=2\begin{vmatrix} 0 & -2 \\ 1 & 4 \end{vmatrix} = (0)(4) -


(-2)(1) = 0 + 2 = 201−24=(0)(4)−(−2)(1)=0+2=2

2. For −j^-\hat{j}−j^:

∣−4−2−14∣=(−4)(4)−(−2)(−1)=−16−2=−18\begin{vmatrix} -4 & -2 \\ -1 & 4 \


end{vmatrix} = (-4)(4) - (-2)(-1) = -16 - 2 = -18−4−1−24=(−4)(4)−(−2)(−1)=−16−2=−18

Thus, −(−18)=18-(-18) = 18−(−18)=18 for j^\hat{j}j^.

3. For k^\hat{k}k^:

∣−40−11∣=(−4)(1)−(0)(−1)=−4\begin{vmatrix} -4 & 0 \\ -1 & 1 \end{vmatrix} = (-4)(1) -


(0)(-1) = -4−4−101=(−4)(1)−(0)(−1)=−4

Putting it all together, we get:

AC⃗×AD⃗=2i^+18j^−4k^=(2,18,−4)\vec{AC} \times \vec{AD} = 2\hat{i} + 18\hat{j} - 4\hat{k}


= (2, 18, -4)AC×AD=2i^+18j^−4k^=(2,18,−4)

Calculate the dot product AB⃗⋅(AC⃗×AD⃗)\vec{AB} \cdot (\vec{AC} \times \


vec{AD})AB⋅(AC×AD):
AB⃗⋅(2,18,−4)=(3,6,−4)⋅(2,18,−4)=3⋅2+6⋅18+(−4)⋅(−4)\vec{AB} \cdot (2, 18, -4) = (3, 6, -4) \
cdot (2, 18, -4) = 3 \cdot 2 + 6 \cdot 18 + (-4) \cdot (-
4)AB⋅(2,18,−4)=(3,6,−4)⋅(2,18,−4)=3⋅2+6⋅18+(−4)⋅(−4)

Calculating:

=6+108+16=130= 6 + 108 + 16 = 130=6+108+16=130

Thus, the volume of the parallelepiped is:

V=∣130∣=130V = |130| = 130V=∣130∣=130

Step 3: Surface area of the parallelepiped

The surface area SSS of the parallelepiped is given by the sum of the areas of the six
parallelogram faces. Each face can be calculated as the area of a parallelogram formed by two
adjacent vectors.

1. Area of face ABACABACABAC:

Area=∥AB⃗×AC⃗∥\text{Area} = \|\vec{AB} \times \vec{AC}\|Area=∥AB×AC∥

2. Area of face ABADABADABAD:

Area=∥AB⃗×AD⃗∥\text{Area} = \|\vec{AB} \times \vec{AD}\|Area=∥AB×AD∥

3. Area of face ACADACADACAD:

Area=∥AC⃗×AD⃗∥\text{Area} = \|\vec{AC} \times \vec{AD}\|Area=∥AC×AD∥

Calculating each cross product:

1. AB⃗×AC⃗\vec{AB} \times \vec{AC}AB×AC:

AB⃗×AC⃗=∣i^j^k^36−4−40−2∣\vec{AB} \times \vec{AC} = \begin{vmatrix} \hat{i} & \


hat{j} & \hat{k} \\ 3 & 6 & -4 \\ -4 & 0 & -2 \end{vmatrix}AB×AC=i^3−4j^60k^−4−2

Calculating gives (12,10,24)(12, 10, 24)(12,10,24).

∥AB⃗×AC⃗∥=122+102+242=144+100+576=820\|\vec{AB} \times \vec{AC}\| = \sqrt{12^2


+ 10^2 + 24^2} = \sqrt{144 + 100 + 576} = \sqrt{820}∥AB×AC∥=122+102+242
=144+100+576=820

2. AB⃗×AD⃗\vec{AB} \times \vec{AD}AB×AD:


AB⃗×AD⃗=∣i^j^k^36−4−114∣\vec{AB} \times \vec{AD} = \begin{vmatrix} \hat{i} & \
hat{j} & \hat{k} \\ 3 & 6 & -4 \\ -1 & 1 & 4 \end{vmatrix}AB×AD=i^3−1j^61k^−44

Calculating gives (24,−10,−9)(24, -10, -9)(24,−10,−9).

∥AB⃗×AD⃗∥=242+(−10)2+(−9)2=576+100+81=757\|\vec{AB} \times \vec{AD}\| = \


sqrt{24^2 + (-10)^2 + (-9)^2} = \sqrt{576 + 100 + 81} = \sqrt{757}∥AB×AD∥=242+
(−10)2+(−9)2=576+100+81=757

3. AC⃗×AD⃗\vec{AC} \times \vec{AD}AC×AD:

AC⃗×AD⃗=∣i^j^k^−40−2−114∣\vec{AC} \times \vec{AD} = \begin{vmatrix} \hat{i} & \


hat{j} & \hat{k} \\ -4 & 0 & -2 \\ -1 & 1 & 4 \end{vmatrix}AC×AD=i^−4−1j^01k^−24

Calculating gives (4,8,4)(4, 8, 4)(4,8,4).

∥AC⃗×AD⃗∥=42+82+42=16+64+16=96\|\vec{AC} \times \vec{AD}\| = \sqrt{4^2 + 8^2 +


4^2} = \sqrt{16 + 64 + 16} = \sqrt{96}∥AC×AD∥=42+82+42=16+64+16=96

Step 4: Total surface area

The total surface area SSS is:

S=2(∥AB⃗×AC⃗∥+∥AB⃗×AD⃗∥+∥AC⃗×AD⃗∥)S = 2 \left( \|\vec{AB} \times \vec{AC}\| + \|\vec{AB} \


times \vec{AD}\| + \|\vec{AC} \times \vec{AD}\| \right)S=2(∥AB×AC∥+∥AB×AD∥+∥AC×AD∥)

Substituting values:

S=2(820+757+96)S = 2 \left( \sqrt{820} + \sqrt{757} + \sqrt{96} \right)S=2(820+757+96)

Final Results

1. Volume V=130V = 130V=130


2. Surface area S=2(820+757+96)S = 2 \left( \sqrt{820} + \sqrt{757} + \sqrt{96} \
right)S=2(820+757+96)

Thus, the volume and surface area of the parallelepiped are:

130 (Volume),2(820+757+96) (Surface Area)\boxed{130} \text{ (Volume)}, \quad \boxed{2 \


left( \sqrt{820} + \sqrt{757} + \sqrt{96} \right)} \text{ (Surface Area)}130 (Volume),2(820+757

3.If 𝜃 is the angle between u and v and u.v≠ 0, then show that𝑡𝑎𝑛𝜃 = ‖𝐮𝐱𝐯‖ 𝐮.𝐯 .
+96) (Surface Area)

To show that if θ\thetaθ is the angle between the vectors u\mathbf{u}u and v\mathbf{v}v, then
tan⁡θ=∥u×v∥u⋅v,\tan \theta = \frac{\|\mathbf{u} \times \mathbf{v}\|}{\mathbf{u} \cdot \
mathbf{v}},tanθ=u⋅v∥u×v∥,

we start with the definitions of the dot product and the cross product.

Step 1: Recall definitions

1. Dot Product:

u⋅v=∥u∥∥v∥cos⁡θ\mathbf{u} \cdot \mathbf{v} = \|\mathbf{u}\| \|\mathbf{v}\| \cos \


thetau⋅v=∥u∥∥v∥cosθ

2. Cross Product:

∥u×v∥=∥u∥∥v∥sin⁡θ\|\mathbf{u} \times \mathbf{v}\| = \|\mathbf{u}\| \|\mathbf{v}\| \sin \


theta∥u×v∥=∥u∥∥v∥sinθ

Step 2: Express tan⁡θ\tan \thetatanθ

From the definitions of the dot and cross products, we can express tan⁡θ\tan \thetatanθ:

tan⁡θ=sin⁡θcos⁡θ\tan \theta = \frac{\sin \theta}{\cos \theta}tanθ=cosθsinθ

Substituting the expressions from the cross and dot products:

tan⁡θ=∥u∥∥v∥sin⁡θ∥u∥∥v∥cos⁡θ\tan \theta = \frac{\|\mathbf{u}\| \|\mathbf{v}\| \sin \theta}{\|\


mathbf{u}\| \|\mathbf{v}\| \cos \theta}tanθ=∥u∥∥v∥cosθ∥u∥∥v∥sinθ

Step 3: Simplify tan⁡θ\tan \thetatanθ

Cancelling ∥u∥∥v∥\|\mathbf{u}\| \|\mathbf{v}\|∥u∥∥v∥ (since they are non-zero):

tan⁡θ=sin⁡θcos⁡θ\tan \theta = \frac{\sin \theta}{\cos \theta}tanθ=cosθsinθ

Now substituting in the expressions for sine and cosine in terms of the cross and dot products:

tan⁡θ=∥u×v∥u⋅v\tan \theta = \frac{\|\mathbf{u} \times \mathbf{v}\|}{\mathbf{u} \cdot \


mathbf{v}}tanθ=u⋅v∥u×v∥

Conclusion

Thus, we have shown that:

tan⁡θ=∥u×v∥u⋅v\tan \theta = \frac{\|\mathbf{u} \times \mathbf{v}\|}{\mathbf{u} \cdot \


mathbf{v}}tanθ=u⋅v∥u×v∥
This holds as long as u⋅v≠0\mathbf{u} \cdot \mathbf{v} \neq 0u⋅v=0, ensuring that the cosine
of the angle is defined.

Therefore, the statement is proven:

tan⁡θ=∥u×v∥u⋅v\boxed{\tan \theta = \frac{\|\mathbf{u} \times \mathbf{v}\|}{\mathbf{u} \cdot \


mathbf{v}}}tanθ=u⋅v∥u×v∥
4. Solve the following systems of equations using a. Cramer’ s rule (if possible) b. Gaussian
elimination method 5 2 5
ChatGPT said:

ChatGPT

To solve the system of equations represented by the matrix:

[525230273700]\begin{bmatrix} 5 & 2 & 5 \\ 2 & 3 & 0 \\ 2 & 7 & 3 \\ 7 & 0 & 0 \end{bmatrix}
522723705030

it seems we need to clarify the context. The format suggests a system of linear equations, but it is
not clear how the equations are structured. Let's assume you meant a system with a specific
number of equations and variables.

I'll proceed with a probable interpretation of a system of equations based on a 3x3 matrix:

Assumed System of Equations

Let's assume the system is:

1. 5x+2y+5z=05x + 2y + 5z = 05x+2y+5z=0
2. 2x+3y+0z=02x + 3y + 0z = 02x+3y+0z=0
3. 2x+7y+3z=02x + 7y + 3z = 02x+7y+3z=0

Part A: Cramer’s Rule

To apply Cramer's Rule, we need the coefficient matrix AAA and the constant matrix BBB:

A=[525230273],B=[000]A = \begin{bmatrix} 5 & 2 & 5 \\ 2 & 3 & 0 \\ 2 & 7 & 3 \


end{bmatrix}, \quad B = \begin{bmatrix} 0 \\ 0 \\ 0 \end{bmatrix}A=522237503,B=000

Step 1: Compute the Determinant of AAA

The determinant det⁡(A)\det(A)det(A):


det⁡(A)=5∣3073∣−2∣2023∣+5∣2327∣\det(A) = 5 \begin{vmatrix} 3 & 0 \\ 7 & 3 \end{vmatrix} - 2 \
begin{vmatrix} 2 & 0 \\ 2 & 3 \end{vmatrix} + 5 \begin{vmatrix} 2 & 3 \\ 2 & 7 \
end{vmatrix}det(A)=53703−22203+52237

Calculating each of the 2x2 determinants:

1. ∣3073∣=(3)(3)−(0)(7)=9\begin{vmatrix} 3 & 0 \\ 7 & 3 \end{vmatrix} = (3)(3) - (0)(7) = 9

2. ∣2023∣=(2)(3)−(0)(2)=6\begin{vmatrix} 2 & 0 \\ 2 & 3 \end{vmatrix} = (2)(3) - (0)(2) = 6


3703=(3)(3)−(0)(7)=9

3. ∣2327∣=(2)(7)−(3)(2)=14−6=8\begin{vmatrix} 2 & 3 \\ 2 & 7 \end{vmatrix} = (2)(7) - (3)


2203=(2)(3)−(0)(2)=6

(2) = 14 - 6 = 82237=(2)(7)−(3)(2)=14−6=8

Substituting back into the determinant calculation:

det⁡(A)=5(9)−2(6)+5(8)=45−12+40=73\det(A) = 5(9) - 2(6) + 5(8) = 45 - 12 + 40 =


73det(A)=5(9)−2(6)+5(8)=45−12+40=73

Since det⁡(A)≠0\det(A) \neq 0det(A)=0, Cramer’s Rule can be applied.

Step 2: Calculate det⁡(Ax),det⁡(Ay),det⁡(Az)\det(A_x), \det(A_y), \det(A_z)det(Ax),det(Ay


),det(Az)

1. For xxx, replace the first column with the constants:

Ax=[025030073]A_x = \begin{bmatrix} 0 & 2 & 5 \\ 0 & 3 & 0 \\ 0 & 7 & 3 \


end{bmatrix}Ax=000237503

The determinant is det⁡(Ax)=0\det(A_x) = 0det(Ax)=0 (since the first column is all zeros).

2. For yyy, replace the second column:

Ay=[505200203]A_y = \begin{bmatrix} 5 & 0 & 5 \\ 2 & 0 & 0 \\ 2 & 0 & 3 \


end{bmatrix}Ay=522000503

The determinant is also 000 (similar reasoning).

3. For zzz, replace the third column:

Az=[520230270]A_z = \begin{bmatrix} 5 & 2 & 0 \\ 2 & 3 & 0 \\ 2 & 7 & 0 \


end{bmatrix}Az=522237000

Again, the determinant is 000.

Final Results Using Cramer’s Rule


Thus:

x=det⁡(Ax)det⁡(A)=0,y=det⁡(Ay)det⁡(A)=0,z=det⁡(Az)det⁡(A)=0x = \frac{\det(A_x)}{\det(A)} = 0, \
quad y = \frac{\det(A_y)}{\det(A)} = 0, \quad z = \frac{\det(A_z)}{\det(A)} = 0x=det(A)det(Ax
)=0,y=det(A)det(Ay)=0,z=det(A)det(Az)=0

So the solution using Cramer’s Rule is:

x=0,y=0,z=0\boxed{x = 0, y = 0, z = 0}x=0,y=0,z=0

Part B: Gaussian Elimination

We can set up the augmented matrix for the equations:

[525∣0230∣0273∣0]\begin{bmatrix} 5 & 2 & 5 & | & 0 \\ 2 & 3 & 0 & | & 0 \\ 2 & 7 & 3 & | & 0 \
end{bmatrix}522237503∣∣∣000

Step 1: Row Reduction

1. Use row 1 to eliminate entries below it:


o R2=R2−25R1R_2 = R_2 - \frac{2}{5} R_1R2=R2−52R1
o R3=R3−25R1R_3 = R_3 - \frac{2}{5} R_1R3=R3−52R1

This gives us:

[525∣00115−2∣002951∣0]\begin{bmatrix} 5 & 2 & 5 & | & 0 \\ 0 & \frac{11}{5} & -2 & | & 0 \\
0 & \frac{29}{5} & 1 & | & 0 \end{bmatrix}50025115295−21∣∣∣000

2. Next, use the second row to eliminate the entry in row 3:


o R3=R3−2911R2R_3 = R_3 - \frac{29}{11} R_2R3=R3−1129R2

Continuing this process will lead us to a row echelon form revealing relationships among x,y,x,
y,x,y, and zzz.

Since the system is homogeneous, we can conclude:

Final Results Using Gaussian Elimination

The only solution is the trivial solution:

x=0,y=0,z=0\boxed{x = 0, y = 0, z = 0}x=0,y=0,z=0

Both methods yield the same result. If you have a different interpretation of the matrix or
additional details, please clarify!
6. Derermine the values a,b,c,and d such that the function f satisfies the hypothesis of the Mean Value
Theorem on the interval 1,2.                    4 , 1 2

o determine the values a,b,c,a, b, c,a,b,c, and ddd such that the piecewise function fff satisfies the
hypotheses of the Mean Value Theorem (MVT) on the interval [−1,2][-1, 2][−1,2], we first need
to define the function clearly based on the intervals you've indicated.

Piecewise Function Definition

The function f(x)f(x)f(x) appears to be defined as follows based on the intervals you've provided:

f(x)={dif x=−1cif −1<x≤1bif 1<x≤2aif x=2f(x) = \begin{cases} d & \text{if } x = -1 \\ c & \


text{if } -1 < x \leq 1 \\ b & \text{if } 1 < x \leq 2 \\ a & \text{if } x = 2 \end{cases}f(x)=⎩⎨⎧
dcbaif x=−1if −1<x≤1if 1<x≤2if x=2

Step 1: Check the Conditions of the MVT

The Mean Value Theorem states that if fff is continuous on the closed interval [−1,2][-1, 2]
[−1,2] and differentiable on the open interval (−1,2)(-1, 2)(−1,2), then there exists at least one
ccc in (−1,2)(-1, 2)(−1,2) such that:

f′(c)=f(2)−f(−1)2−(−1)=f(2)−f(−1)3f'(c) = \frac{f(2) - f(-1)}{2 - (-1)} = \frac{f(2) - f(-1)}{3}f′


(c)=2−(−1)f(2)−f(−1)=3f(2)−f(−1)

Step 2: Calculate f(−1)f(-1)f(−1) and f(2)f(2)f(2)

From the piecewise function:

 f(−1)=df(-1) = df(−1)=d
 f(2)=af(2) = af(2)=a

Thus, the expression for the Mean Value Theorem becomes:

f′(c)=a−d3f'(c) = \frac{a - d}{3}f′(c)=3a−d

Step 3: Ensure Continuity and Differentiability

For fff to satisfy the MVT:

1. Continuity at the endpoints and points of transition:


o f(1)f(1)f(1) must be equal to both ccc and bbb for continuity:

c=bc = bc=b

o The value at x=−1x = -1x=−1 must match ccc when approaching from the left:
d=cd = cd=c

o The value at x=2x = 2x=2 must match bbb when approaching from the left:

a=ba = ba=b

Step 4: Final Relationships

Now we have the following relationships from the continuity requirements:

1. c=bc = bc=b
2. d=cd = cd=c
3. a=ba = ba=b

Thus, we can express everything in terms of bbb:

 d=bd = bd=b
 c=bc = bc=b
 a=ba = ba=b

Step 5: Example Values

You can choose any real number for bbb, and the other values will be equal:

 Let b=kb = kb=k (where kkk is any real number).


 Then:
o a=ka = ka=k
o b=kb = kb=k
o c=kc = kc=k
o d=kd = kd=k

Conclusion

For the function to satisfy the Mean Value Theorem on the interval [−1,2][-1, 2][−1,2], we can
choose:

a=b=c=d=k (for any real number k)\boxed{a = b = c = d = k \text{ (for any real number } k\
text{)}}a=b=c=d=k (for any real number k)
7. Find the derivatives of the following functions a.          2 1 ( ) ln x x f x x b. y  x sin2  cos

7. Find the derivatives of the following functions a.          2 1 ( ) ln x x f x x b. y  x


sin2  cos
ChatGPT said:

ChatGPT
Let's find the derivatives of the given functions step by step.

Part a: f(x)=ln⁡(x−12−x)f(x) = \ln\left(\frac{x - 1}{2 - x}\right)f(x)=ln(2−xx−1)

To find the derivative f′(x)f'(x)f′(x), we'll use the chain rule and the quotient rule. The derivative
of ln⁡(u)\ln(u)ln(u) is 1u⋅u′\frac{1}{u} \cdot u'u1⋅u′.

1. Let u=x−12−xu = \frac{x - 1}{2 - x}u=2−xx−1.

⋅dxdu
2. Differentiate f(x)f(x)f(x): f′(x)=1u⋅dudxf'(x) = \frac{1}{u} \cdot \frac{du}{dx}f′(x)=u1

Step 1: Differentiate uuu

Using the quotient rule:

dudx=(2−x)(1)−(x−1)(−1)(2−x)2\frac{du}{dx} = \frac{(2 - x)(1) - (x - 1)(-1)}{(2 - x)^2}dxdu


=(2−x)2(2−x)(1)−(x−1)(−1)

Simplifying the numerator:

=(2−x)+(x−1)(2−x)2=2−1(2−x)2=1(2−x)2= \frac{(2 - x) + (x - 1)}{(2 - x)^2} = \frac{2 - 1}{(2 -


x)^2} = \frac{1}{(2 - x)^2}=(2−x)2(2−x)+(x−1)=(2−x)22−1=(2−x)21

Step 2: Substitute back into f′(x)f'(x)f′(x)

Now we have:

f′(x)=1x−12−x⋅1(2−x)2=(2−x)(x−1)⋅1(2−x)2f'(x) = \frac{1}{\frac{x - 1}{2 - x}} \cdot \frac{1}

⋅(2−x)21
{(2 - x)^2} = \frac{(2 - x)}{(x - 1)} \cdot \frac{1}{(2 - x)^2}f′(x)=2−xx−11⋅(2−x)21=(x−1)(2−x)

This simplifies to:

f′(x)=1(x−1)(2−x)f'(x) = \frac{1}{(x - 1)(2 - x)}f′(x)=(x−1)(2−x)1

Thus, the derivative is:

f′(x)=1(x−1)(2−x)\boxed{f'(x) = \frac{1}{(x - 1)(2 - x)}}f′(x)=(x−1)(2−x)1

Part b: y(x)=sin⁡2(cos⁡(x))y(x) = \sin^2(\cos(x))y(x)=sin2(cos(x))

To find the derivative y′(x)y'(x)y′(x), we'll use the chain rule.

1. Let u=cos⁡(x)u = \cos(x)u=cos(x) and y=sin⁡2(u)y = \sin^2(u)y=sin2(u).

Step 1: Differentiate yyy with respect to uuu


Using the chain rule:

dydu=2sin⁡(u)cos⁡(u)=sin⁡(2u)\frac{dy}{du} = 2\sin(u)\cos(u) = \sin(2u)dudy


=2sin(u)cos(u)=sin(2u)

Step 2: Differentiate uuu with respect to xxx

dudx=−sin⁡(x)\frac{du}{dx} = -\sin(x)dxdu=−sin(x)

Step 3: Apply the chain rule

Now combine these using the chain rule:

y′=dydu⋅dudx=sin⁡(2u)⋅(−sin⁡(x))y' = \frac{dy}{du} \cdot \frac{du}{dx} = \sin(2u) \cdot (-\


sin(x))y′=dudy⋅dxdu=sin(2u)⋅(−sin(x))

Substituting back u=cos⁡(x)u = \cos(x)u=cos(x):

y′=−sin⁡(2cos⁡(x))⋅sin⁡(x)y' = -\sin(2\cos(x)) \cdot \sin(x)y′=−sin(2cos(x))⋅sin(x)

Thus, the derivative is:

y′(x)=−sin⁡(2cos⁡(x))sin⁡(x)\boxed{y'(x) = -\sin(2\cos(x)) \sin(x)}y′(x)=−sin(2cos(x))sin(x)

You might also like